2013
DOI: 10.1186/1129-2377-14-87
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality in population surveys of headache prevalence, burden and cost: key methodological considerations

Abstract: Population-based studies of headache disorders are important. They inform needs assessment and underpin service policy for a set of disorders that are a public-health priority. On the one hand, our knowledge of the global burden of headache is incomplete, with major geographical gaps; on the other, methodological differences and variable quality are notable among published studies of headache prevalence, burden and cost.The purpose here was to start the process of developing standardized and better methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 125 publications
0
35
1
Order By: Relevance
“…They are the main reason for patient visits to neurologists' offices, and it is one of the most frequent symptoms reported to primary care physicians . Epidemiological studies are important to understand the scope and scale of headache in specific areas or countries, in order to better know its causes, mechanisms, natural history and comorbidities, to estimate its burden to individuals and to societies, and to help health care providers and government authorities to appropriately spend their resources, accepting headache disorders as a public health priority …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They are the main reason for patient visits to neurologists' offices, and it is one of the most frequent symptoms reported to primary care physicians . Epidemiological studies are important to understand the scope and scale of headache in specific areas or countries, in order to better know its causes, mechanisms, natural history and comorbidities, to estimate its burden to individuals and to societies, and to help health care providers and government authorities to appropriately spend their resources, accepting headache disorders as a public health priority …”
mentioning
confidence: 99%
“…Merikangas, in a review of recent publications of migraine prevalence, utilizing exclusively the International Classification of Headache Disorders‐II criteria, found an aggregated rate of 11.5%. A group of experts, led by Lifting the Burden, a nongovernmental organization conducting the Global Campaign Against Headache, has published recently some guidelines in an attempt to standardize the methodology of epidemiological studies on headache . This group highlights the crucial role of population‐based studies as a meaningful way of quantifying the headache problem, as a starting point for public health care planning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors that influence quality have been noted to be inadequately addressed in past studies [3]. These, and others of potential importance, are made the subject of recommendations accompanied by detailed explanatory commentary.…”
Section: Discussionmentioning
confidence: 99%
“…Such conditions are currently dichotomised into two broad categories, primary (benign), and secondary (serious), where the former occurrences are relatively common and the latter constitute only around 10% of all known cases [7]. Although epidemiological and impact studies of headache remain incomplete [8], it is indicated that the combined prevalence of headache conditions is set at around 50% of the global population, rendering an economic impact estimated to be £500 million per annum in the UK and between $5.6 and $17.2 billion in the United States alone [9]. Correspondingly, headache conditions account for one of the most common complaints within primary and neurological care settings, with a significant proportion of sufferers choosing not to seek medical attention [10] and therefore remaining unreflected in the estimates.…”
Section: Introductionmentioning
confidence: 99%